TATA KELOLA PEMERINTAHAN YANG RESPONSIF DI DESA BANING KOTA KECAMATAN SINTANG - Hahury, Jhony Fredy (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Responsive village governance is integral to the implementation of good governance, aimed at establishing a government that effectively addresses community issues, needs, and services. This study seeks to describe and analyze responsive governance in Baning Kota Village, Sintang District. Findings indicate that the Baning Kota Village Government has successfully adopted responsive governance through development programs, empowerment initiatives, and public services. The community has notably acknowledged efforts to accelerate development, empowerment, and access to services. However, village officials encounter challenges such as limited knowledge of information technology and insufficient community participation in village forums. Consequently, achieving responsive governance necessitates a robust commitment from all stakeholders, including the village government, the Village Consultative Body (BPD), and the community, to synergize and enhance collaboration, thereby fostering public trust in an effective and progressive village government and development programs.